WHALING IN THE ANTARCTIC: CASE REVIEW AUSTRALIA VS. JAPAN, NEW ZEALAND INTERVENIENT - INTERNATIONAL COURT OF JUSTICE - Leite, Brenda Lima; Santos, Livian Mariane Coelho dos; Ferreira, Adriano Fernandes (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2022)
The present article aims to analyze the specific case of Whales in Antarctica whose demand was registered in the International Court of Justice by Australia in the face of Japan and had New Zealand as an intervener. The work provides a brief introduction on the emergence of international legislation for the protection of whales, the facts of the specific case and the synthetic analysis of the points demanded by Australia observed in the Court and the points that the Court does not use in the end. In addition, select a method used by CIJ in this case, which is the review criterion (standard of review), as well as the main aspects of the dissenting votes and the separate vote of Judge Cançado Trindade. In the end, the article brings a critical analysis of the CIJ's decision in this emblematic case, as well as information about the importance of cetaceans in the marine ecosystem and their condition as a diffuse title legal asset. O presente artigo tem como objetivo analisar o caso concreto Caça de Baleias na Antártica cuja demanda foi apresentada perante a Corte Internacional de Justiça pela Austrália em face do Japão e que teve a Nova Zelândia como interveniente. O trabalho traz breve introdução acerca do surgimento da legislação internacional de proteção às baleias, os fatos do caso concreto e analisa sinteticamente os pontos demandados pela Austrália perante a Corte e os pontos que a Corte utilizou no julgamento final. Ademais, aponta-se a metodologia utilizada pela CIJ neste caso, qual seja o critério de revisão (standard of review), bem como os aspectos principais dos votos dissidentes e do voto separado do Juiz Cançado Trindade. Ao final, o artigo traz uma análise crítica da decisão da CIJ neste caso emblemático, tal como insights acerca da importância dos cetáceos no ecossistema marinho e sua condição como bem jurídico de titularidade difusa.